Pengaruh Aksesibilitas, Sistem Pengendalian Internal Pemerintah, Transparansi, Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa - Doyosi, Riri Putri; Abdullah, Abdullah; Fadli, Fadli (Wahana Riset Akuntansi, 2023)
AbstractPurpose – This purpose of this study is to examine the accountability of village fund management in terms of accessibility, government internal control system, transparency and use of information technology.Design/methodology/approach – This study used a survey method through the distribution of questionnaires conducted in 49 villages spread across 6 sub-districts in Lebong regency, with a total of 49 village treasurer respondents. The relationship between variables was analyzed using SPSS.Findings – The results of multiple regression analysis shows that 1) Accessibility has a negative influence on the accountability of des fund management. 2) The government's internal control system has a positive influence on accountability of village fund management. 3) Transparency has a positive influence on the accountability of village fund management. 4) Utilization information technology has a positive influence on the accountability of village fund management.Originality/value –  This research is aimed at village governments regarding village financial management. This was done to see more clearly the form of accountability of village governments in managing village funds, where there are still many village governments that cannot be accountable for village funds, especially Lebong district. As well as explaining how the government's internal control system, accessibility, transparency and use of information technology explain the accountability of village fund managementResearch limitations/implications – The limitation of this research is that the statements in the accessibility questionnaire are still inaccurate in explaining the accessibility variables. The implication of this research is to prove that agency theory in line with the variables of accessibility, internal control system, transparency and use of information technology related to accountability village fund management. According to the results of this research, it is hoped that it can provide benefits for the village government as a reference or material for consideration in making decisions regarding the importance of responsible management village funds and as a consideration in making policies for increasing accountability of village funds.Keywords: Accessibility, accountability of village fund management, government internal control system, transparency, utilization of information technology.Article Type: Research Paper